The Acute Effects of Dynamic and Static Stretching on Tennis Serve Targeting Performance - Bahar Yılmaz; Asuman Şahan; Bülent Turna (Selcuk University, 2020)
The study investigates the acute effects of dynamic and static stretching on the tennis serve targeting performance of amateur tennis players. Twenty male athletes who were between the ages of 16-24 years and played tennis for at least 1 year (21.40±2.16 years, 181±0.06 cm, 71.85±7.42 kg, tennis playing time 1.55±0.88 years) voluntarily participated in the study. Prior to the pre-tests and after applying the traditional warm-up protocol, serve targeting test (STT) was applied to all participants. In the post-tests, STT was used after applying three different warm-up methods on three different days (48-hour rest interval). The warm-up stages included No Treatment (NT) (jogging, rally), Static Stretching (SS) and Dynamic Stretching (DS). In the statistical analysis, the homogeneity of the data was investigated using the Shapiro Wilk test. The Wilcoxon test was used to compare the pre-test and post-test results of the non-homogeneous data; Friedman test was used to compare the three different stretching methods with each other; in the paired comparisons of the groups, the paired samples t-test was used for the homogenous data and Wilcoxon test was used for the non-homogeneous data. In conclusion, stretching exercises before serving increased the serve targeting performance and the increase in the dynamic stretching exercises was higher than that in static stretching exercises.